HOW DIGITAL MARKETING INFLUENCES IMPULSE BUYING TENDENCY AND IMPULSE BUYING IN E-COMMERCE INDUSTRY - Patria Laksamana & Gusrianda Hidayat (International Journal of Research Science and Management, 2019)
The study examines the impact of digital marketing that includes social media marketing and content marketing on impulse buying tendency and impulse buying. The context of the study was e-commerceindustry in Indonesia and a questionnaire was developed with 208 respondents. The results confirm that social media marketing and content marketing partially do not affect both on impulse buying tendency and impulse buying. The results also reveal that social media marketing and content marketing simultaneously affecting impulse buying tendency. Hence, impulse buying affected by impulse buying tendency.